Development of an Integrated Digital Audit System for Modular and Multi-Role-Based Higher Education Accreditation Document Management - Bahri, Alim; Wardhani, Rulyanti Susi; Yunita, Anggraini (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2026)
Program accreditation is a strategic process in higher education that requires transparency, efficiency, and cross-unit collaboration. Common challenges include the complexity of document management, coordination between parties, and the potential for administrative errors. This research developed a web-based accreditation information system that is modular and supports various roles, namely administrators, study programs, the Institute for Learning Development and Quality Assurance (LP3M), and auditors. This system enables structured management of LED (Self-Evaluation Reports) and LKPS (Program Study Performance Reports), equipped with LP3M validation features, auditor comments, revision history, and audit trails to ensure accountability at every stage. The results of implementation show an increase in the efficiency of the accreditation process, a reduction in administrative errors, and an increase in transparency and accountability between units. Additionally, this system strengthens coordination between study programs and quality assurance institutions, making the accreditation process more integrated and controlled. Research findings confirm that this system is not only relevant for the developing institution but can also be replicated in other universities facing similar challenges. Thus, this web-based accreditation information system has the potential to be an innovative solution in supporting sustainable higher education quality management.